ChemInform Abstract: Coordination Polymers Built from 1, 4‐Bis(imidazol‐1‐ylmethyl)benzene: from Crystalline to Amorphous. Issue 36 (August 2016) - Adarsh, N. N.; Novio, Fernando; Ruiz‐Molina, Daniel
Abstract: Review: 85 refs.